Structural and molecular characterization of human FK506-binding protein 25 (FKBP25), a nuclear immunophilin - Prakash, Ajit (2016)
Human FK506 binding protein (FKBP25), a 25 kDa nuclear protein, is a member of the FK506-binding protein family with peptidyl-prolyl cis-trans isomerase (PPIase) activity. It has a conserved C-terminal FK506 binding domain (FKBD), which binds with immunosuppressive drugs such as FK506 and rapamycin and a unique N-terminal helix-loop-helix domain (HLH). These two domains are linked through a long flexible loop. FKBP25 is known to interact with proteins like Nucleolin, MDM2, YY1 and most importantly HDAC1/2. While the structures of two the individual domains of human FKBP25 are known, the structure of full-length FKBP25 and the molecular mechanism of its interaction with nucleic acids remain unknown. The main objective of this thesis research is to perform the structural and molecular characterization of FKBP25 in order to explore the mechanism of its interaction with other proteins, nucleic acids and drugs with an aim of delineating its molecular function. In this study, we determined the crystal structure of human FKBD25 in complex with FK506 drug and attempted to explore the mechanism by which FKBP25 shows differential binding affinity to FK506 and rapamycin (200-fold higher affinity), which is unique feature of FKBP25 among other FKBPs. Later we also determined the nuclear magnetic resonance (NMR) solution structure of the human full-length FKBP25. The topology of FKBP25 showed that the HLH and FKBD are connected by a long and unstructured flexible linker between the domains. The N-terminal domain consists of five α-helices (Helix-Loop-Helix domain), whereas the C-terminal domain shows a canonical FKBD fold which consists of six antiparallel β-strands and a short central α-helix. Further using gel shift assay, we showed that FKBP25 can interact with DNA in sequence-independent manner. This binding was confirmed by biophysical assays including isothermal titration calorimetry (ITC), tryptophan fluorescent quenching and NMR experiments. The binding affinity was estimated around 1.23 μM. We then identified the DNA binding site on FKBP25 by NMR titration and confirmed that mutations of some of the amino acids from the DNA binding site caused reduced DNA binding. We also observed intermolecular NOEs between FKBP25 and DNA. Based on multinational studies and NMR data, we performed docking of FKBP25 with DNA. The FKBP25-DNA complex model revealed that both N-terminal domain and the basic loop of the C-terminal domain are important for nucleic acid recognition. Sequence alignment of FKBP25 with other human FKBPs and homologs of FKBPs showed that the basic loop is exclusively present in human FKBP25 and could be important for nucleic acid binding. The fourth helix of the HLH domain forms major-groove interactions and the basic FKBD loop cooperates to form interactions with an adjacent minor-groove of DNA. The FKBP25-DNA complex model provides structural and mechanistic insights into the nuclear immunophilin-mediated nucleic acid recognition